1988
DOI: 10.1007/bf00334704
|View full text |Cite
|
Sign up to set email alerts
|

An asparaginase of Aspergillus nidulans is subject to oxygen repression in addition to nitrogen metabolite repression

Abstract: Of five amidohydrolase activities subject to nitrogen metabolite repression in Aspergillus nidulans, L-asparaginase shows clearest evidence of also being subject to repression by atmospheric oxygen. Such oxygen repressibility is only evident under nitrogen metabolite derepressed conditions. Asparaginase levels are also considerably elevated by areA300, an altered function allele of the positive acting wide domain regulatory gene areA mediating nitrogen metabolite repression and are drastically reduced by loss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Probably the most extraordinary areA mutation is areA300, which not only leads to nitrogen metabolite derepression of several activities, including nitrate and nitrite reductases, but also relieves repression of asparaginase and thymine 7-hydroxylase syntheses by atmospheric oxygen while reducing expression of certain other structural genes (32,163,164). areA 300 is an "in frame" 417-bp tandem duplication that includes the whole DNA-binding region and extending 74 codons 3' to it (32).…”
Section: Nitrogen Metabolite Repressionmentioning
confidence: 99%
“…Probably the most extraordinary areA mutation is areA300, which not only leads to nitrogen metabolite derepression of several activities, including nitrate and nitrite reductases, but also relieves repression of asparaginase and thymine 7-hydroxylase syntheses by atmospheric oxygen while reducing expression of certain other structural genes (32,163,164). areA 300 is an "in frame" 417-bp tandem duplication that includes the whole DNA-binding region and extending 74 codons 3' to it (32).…”
Section: Nitrogen Metabolite Repressionmentioning
confidence: 99%
“…(Foda et al, 1980), Rhodosporidium toruloides (Ramakrishnan and Joseph, 1996) were reported to produce L-asparaginase. L-Asparaginase from fungal sources such as Aspergillus nidulans (Shaffer et al, 1988) using different synthetic substrates and Aspergillus terreus isolated from decomposing vegetables were not toxic and appeared to have myelosuppressive and immunosuppressive activity (Ali et al, 1994). Mesophilic fungus Cylindrocarpon obtusisporum MB-10 (Rahae et al, 1990), Aspergillus tamari and Aspergillus terreus (Sarquis et al, 2004;, Aspergillus niger (Mishra., 2006) and Aspergillus sp.…”
Section: Introductionmentioning
confidence: 98%
“…1). The heterozygous diploid torA3/torA ϩ showed increased sensitivity to 10 mM DL-aspartic acid ␤-hydroxamate in the presence of NH 4 ϩ , indicating partial derepression of the asparaginase gene ahrA (11,27). Both fprA Ϫ and jipA Ϫ showed weak pleiotropic effects on several nitrogen sources and had severely reduced growth on 2-pyrrolidone.…”
mentioning
confidence: 99%